Photoluminescence studies of the interface of CdS/CdTe heterojunctions [Articol] - Vatavu, Sergiu; Zhao, Hehong; Caraman, Iuliana; Gașin, Petru; Morel, Don; Ferekides, Chris (My University, 2009)
The photoluminescence analysis of CdS/CdTe interface layer of CdS/CdTe heterojunction has been carried out in the 15- 100 K temperature range. An attempt to correlate observed PL features with the CdSxTe1–x layer presence at the interface of the heterojunctions was made. It is assumed the 1.525 eV band has an excitonic origin and 1.37X PL band is a characteristic impurity band due to CdSTe layer. Comparative plots showing SnO2/CdTe PL spectra are given as well.
VATAVU, Sergiu; Hehong ZHAO; Iuliana CARAMAN; Petru GAȘIN; Don MOREL și Chris FEREKIDES. Photoluminescence studies of the interface of CdS/CdTe heterojunctions. Physica Status Solidi. 2009, nr.5. pp.1299-1302. ISSN 1862-6351.